Large Polaron Condensation in a Pseudo-Bilayer Quantum Hall Composite - Bo Dai; Changyue Wang; Junhao Chen; Xin Su; Yuning Shi; Yihan Zeng; Ying Wang; Kai Chen (Nanomaterials, 2024)
There is much interest regarding the “coupled ferroelectricity and superconductivity” in the two-dimensional material, bilayer Td-MoTe2; however, the value and the type of electric polarization are unknown. The device structure and the measurement method show that the measured material is the composite of the pseudo-bilayer quantum Hall system, with a thickness of about thirty-six nanometers. The derived dielectric hysteresis loops and the calculated electronic structure reveal that the condensed large polarons are responsible for the reverse ferroelectricity and the coupled superconductivity. The maximum value of polaron-type electric polarization is ~12 nC/μm2 or 1.2 × 104 μc/cm2.